(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Construction of foundation of bridges in remote hilly terrain, in adverse climatic condition, is very difficult due to the limited working period and unavailability of transportation of machinery and equipment. In such situations where regular pile foundation is not feasible, micro-piles prove to be better solution. The study deals with the conditions in the field, field testing of micro-piles and their applicability as bridge foundation. In remote areas and difficult hilly terrains there are several problems faced during construction of bridges. The hilly atmosphere has oxygen deficiency, negative temperatures, chilling cold, snowfall, frozen water bodies, lack of adequate transportation facilities and roads are some of the innumerable problems faced during construction. A number of environmental conditions allow only a limited period for construction which is hardly four-five hours a day. Considering the terrain and hydraulic factors at suchsites there is limited option of foundation for the bridges. Usually such terrain has cobbles/gravels in the river bed. The seepage rate is likely to be very high. The high seepage rate requires heavy de-watering works while undertaking construction of substructure. Also such heavy concreting will be time consuming. Since, the time slot for construction is limited, regular procedures do not work. Based on scour criteria, for such heavy loads as on bridges deep foundations are suitable but boulders, cobbles in such area do not allow sinking of well foundation, leaving us with only one option – piles. However, due to limited transportation facilities, roadways, it is not possible to transport such heavy rigs to such remote and inaccessible areas. Therefore, micro-piles are the most suitable option for bridge foundation considering all the above factors and limitations. A micro-pile is a small-diameter drilled and grouted non-displacement pile that is typically reinforced. It is constructed by drilling a borehole, placing steel reinforcement, and grouting the hole and can bear axial loads as well as lateral loads. They are suitable and can be installed in restrictive areas and in all soil types and ground conditions. In India, the use of micro-piles has been restricted only to slope stabilization in hydro projects and earth retaining structures and not in bridge foundation and therefore, it will be a new area for future endeavors.